If it's not what You are looking for type in the equation solver your own equation and let us solve it.
d/3+1=2
We move all terms to the left:
d/3+1-(2)=0
We add all the numbers together, and all the variables
d/3-1=0
We multiply all the terms by the denominator
d-1*3=0
We add all the numbers together, and all the variables
d-3=0
We move all terms containing d to the left, all other terms to the right
d=3
| 3(2e+4)=6e+12 | | 24=k273/2 | | x/100=15/40 | | 6(y+2)-4(y-1)=26 | | 210x=-675 | | 2x+(3x-1)=(137-x) | | 4=2-5b/7 | | 3.1=-4.7v-1.5v | | 2b/7-2=4 | | b/7+2=4 | | 3(t+1)=2t-6 | | -3t+5=0 | | 63=9b+54 | | 320r=2104 | | -1/6n=-1/15 | | 6x3=(9x5)-(9x2) | | (2-2x)/11=-12 | | 2(x-x)=36 | | 4t=-7+2t | | -29/12=-3/2n+3/2=7/6 | | .2+2.1x-2.6=9.15 | | -3.1=-4.7v-1.5v | | -3t-21=-15 | | -320r=570+254=1788 | | -3.2r-5.7+2.54=-17.88 | | 1/2n-2/3n=-1/15 | | 12(t+2)=25 | | -45/4=23/6p+4/3+6/5p | | -8(x+2)=(2x+16) | | 8=3/4a+12-1a+4 | | 3(5x+3)=-111 | | 12t-5=8t+3 |